DEWAN DJAMBI SEMENTARA: MENEGOSIASIKAN ULANG KESULTANAN JAMBI MASA REVOLUSI INDONESIA 1945-1949 - Kurohman, M Taofik; Tangkilisan, Yuda B; Abdurakhman, Abdurakhman (Handep: Jurnal Sejarah dan Budaya, 2023)
The independence revolution in Jambi was distinct from the spirit of social revolution in other regions. A sense of disappointment among Jambi's traditional elites towards the new Republican elites from outside Jambi caused local political conflict in Jambi. Accordingly, the narrative of the restoration of the Jambi Sultanate, which had been destroyed during the Jambi War of 1900-1907, emerged. Political efforts were made between the Jambi Government and the Government of the Republic of Indonesia or the Netherlands to solve political problems in Jambi. Using historical methods that focus on the process and time, the study shows that the Dewan Djambi Sementara was a council to make Jambi a particular region in the federal system, which the Dutch established at that time. The primary demand of the Dewan Djambi Sementara was to make Jambi an autonomous region by restoring the Jambi Sultanate and separating it from the Central Sumatra Province formed by the Government of the Republic of Indonesia. However, the demands of the Dewan Djambi Sementara were not accomplished because the Dutch hesitantly supported forming a region with a feudal system. In addition, political developments between the Republic of Indonesia and the Dutch, described in the Roem-Royen agreement, hindered the process. The demands for the sultanate restoration and the granting of autonomous rights vanished along with the administrative transfer from the Netherlands to the Republic of Indonesia due to the Round Table Conference in The Hague. Despite this setback, the spirit of Jambi regionalism that demanded regional autonomy was continued in youth and regional organizations during the Republic of Indonesia era. The endeavors of these organizations eventually made an autonomous region at the provincial level in 1957